2018
DOI: 10.1088/1475-7516/2018/12/031
|View full text |Cite
|
Sign up to set email alerts
|

Oscillation modes of hybrid stars within the relativistic Cowling approximation

Abstract: The first direct detection of gravitational waves has opened a new window to study the Universe and would probably start a new era: the gravitational wave Astronomy. Gravitational waves emitted by compact objects like neutron stars could provide significant information about their structure, composition and evolution.In this paper we calculate, using the relativistic Cowling approximation, the oscillations of compact stars focusing on hybrid stars, with and without a mixed phase in their cores. We study the ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
78
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 100 publications
11
78
2
2
Order By: Relevance
“…The hybrid magnetised EoS was obtained by combining the GM1L parametrisation of the RMF model for the hadron phase and the FCM model for the quark phase. Although it has been already shown that the hybrid EoS GM1L+FCM without MF satisfies the observational mass constraint of 2M (see, for example,Ranea-Sandoval et al (2018); Orsaria et al(2019)), we have extended the study of hybrid stars considering the effect of the MF on the EoS describing their matter composition. Our results show that both the 2M limit and the tidal deformability constraint are verified both when magnetized GM1L hadronic EoS or magnetised GM1L+FCM hybrid EoS are used.…”
mentioning
confidence: 99%
“…The hybrid magnetised EoS was obtained by combining the GM1L parametrisation of the RMF model for the hadron phase and the FCM model for the quark phase. Although it has been already shown that the hybrid EoS GM1L+FCM without MF satisfies the observational mass constraint of 2M (see, for example,Ranea-Sandoval et al (2018); Orsaria et al(2019)), we have extended the study of hybrid stars considering the effect of the MF on the EoS describing their matter composition. Our results show that both the 2M limit and the tidal deformability constraint are verified both when magnetized GM1L hadronic EoS or magnetised GM1L+FCM hybrid EoS are used.…”
mentioning
confidence: 99%
“…a full pasta phase calculation, must be used taking into account the formation of phase structures in the mixed phase [138]. Recently, several works have included finite-size effects at the hadron-quark phase transition in a phenomenological way, mimicking the mixed phase by a function which depends on the broadening of the phase transition [30,131,139]. Therefore, the Gibbs construction for the mixed phase can be simulated through a continuous interpolation between the hadronic and quark phases to mimic the mixing or percolation [30].…”
Section: Dense Hybrid-matter In Nss Structurementioning
confidence: 99%
“…Moreover, as shown in Refs. [30,[250][251][252][253] the g-mode frequency strongly depends on the amplitude of the discontinuity, as it is shown in figure 9. Thus, it could be used to infer the value of the density jump and shed some light on the properties of the hadron-quark transition.…”
Section: Exotic Stars Hss and Oscillation Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…The universal relationship proposed in Ref. [30] between x CSS ≡ ∆ / trans , one of parameters of the Constant Speed of Sound (CSS) parametrization for quark matter [53,77], and the frequency of the g-modes. The original fitting function is y old fit = c old 1 log(x CSS ) + c old 2 with c old 1 = 0.454 ± 0.031 and c old 2 = 0.235 ± 0.023.…”
Section: Stellar Oscillationsmentioning
confidence: 99%